Strategic CSR: A Concept Building Meta‐Analysis - Vishwanathan, Pushpika; van Oosterhout, Hans (J.); Heugens, Pursey P. M. A. R.; Duran, Patricio; van Essen, Marc (Journal of Management Studies, 2020)
AbstractThis study develops the concept of Strategic Corporate Social Responsibility (Strategic CSR) by meta‐analyzing the available empirical evidence on the relationship between CSR and corporate financial performance (CFP). Using meta‐analytic structural equation modeling on effect size data from 344 primary studies, our study documents four empirical mechanisms explaining how CSR positively affects CFP: by 1) enhancing firm reputation, 2) increasing stakeholder reciprocation, 3) mitigating firm risk, and 4) strengthening innovation capacity. We propose these four mechanisms to identify four causally relevant attributes that allow us to conceptually distinguish Strategic CSR from CSR more generally. Our findings indicate that the four mechanisms combined explain 20 per cent of the CSR‐CFP relationship, suggesting that considerable room remains for future empirical research. The development of an empirically informed, causal conceptualization of Strategic CSR responds to a long‐heard call for better‐specified concepts in empirical CSR research.